2016
DOI: 10.1038/srep19815
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat choice in island lizards enhances camouflage against avian predators

Abstract: Camouflage can often be enhanced by genetic adaptation to different local environments. However, it is less clear how individual behaviour improves camouflage effectiveness. We investigated whether individual Aegean wall lizards (Podarcis erhardii) inhabiting different islands rest on backgrounds that improve camouflage against avian predators. In free-ranging lizards, we found that dorsal regions were better matched against chosen backgrounds than against other backgrounds on the same island. This suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 54 publications
3
65
0
3
Order By: Relevance
“…Many recent studies have shown animals are able to integrate information about their own appearance and their surroundings to modulate behaviour and reduce predation risk [27][28][29][30][31]. Studies addressing the interaction between colour and behaviour in signalling are rarer, but they too show that animals have the capacity to select display locations and orientations that improve signal effectiveness [5,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have shown animals are able to integrate information about their own appearance and their surroundings to modulate behaviour and reduce predation risk [27][28][29][30][31]. Studies addressing the interaction between colour and behaviour in signalling are rarer, but they too show that animals have the capacity to select display locations and orientations that improve signal effectiveness [5,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Together with our findings that red pattern does not differ with beetle length, this suggests that the less common adoption of a typical conspicuous color, red, by polyphagous species, could be to limit conspicuousness when they feed on diverse backgrounds. Recent studies of lizards (Marshall et al, 2016) and crabs (Uy et al, 2017) indicate that animals actively choose to match their background. As the spectral sensitivities of chrysomelids appear to be limited to UV, blue and green but not red (Sharkey et al, 2017), active background matching may not fully explain color pattern differences of beetles with their host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Colour change (Umbers et al ., ; Duarte, Flores & Stevens, ), substrate selection in relation to phenotype (e.g. Kang et al ., ; Kjernsmo & Merilaita, ; Lovell et al ., ; Marshall, Philpot & Stevens, ; Smithers et al ., ), and orientation behaviour to match the orientation of substrate textures (Kang et al ., , ,b), are also powerful evidence for the importance of background matching for concealment (see review by Stevens & Ruxton, ).…”
Section: Peeling the Onionmentioning
confidence: 99%